Pengaruh Media Video Animasi Dua Dimensi (2D) Terhadap Hasil Belajar IPAS Materi Siklus Air - Auliya Puteri Hapsari; Iqnatia Alfiansyah; Nataria Wahyuning Subayani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to describe the effect of two-dimensional (2D) animation video media on the results of learning science on the water cycle material. The method used in this study is the experimental method with a quasi-experimental type. The design in this study is a non-equivalent control group design. The design of this study involved two classes, the experimental class, namely class V B, which was taught using two-dimensional (2D) animation video media and the control class, namely class V A, which was taught without using two-dimensional (2D) animation video media. The sample used was students in classes V A and V B of UPT SD Negeri 57 Gresik totaling 54 students. The data collection technique used a learning outcome test. Based on the results of the research on the Independent Sample T-test which showed a Sig. (2-tailed) value of 0,000 which means ≤ 0,05 then is rejected and is accepted which means there is an influence of two-dimensional (2D) animation video media on the results of learning science on the water cycle material.